Fuzzy Logic based Object Function to Enhance the Quality of Service in Internet of Things - Arivubrakan, P.; Kanagachidambaresan, G. R. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Internet of Things (IoT) is a developing field, which more number of smart devices are connected together in the resource constrained environment. The routing technique provides an intelligent path between the sender and sink node. Routing Protocol for Low Power Lossy (RPL) Network is the standardized routing protocol in the IoT environment. It has some limitation especially while choosing the best parent among the multiple nodes. By default in RPL, there are two standard objective functions, Minimum Rank with Hysteresis Objective Function (MRHOF) and Objective Function Zero (OF0) which have single metric to select the best parent node. Our Proposed method involves Fuzzy Logic based Objective Functions (FLOF) which includes the four metrics such as Hop count, Energy, Signal Strength and ETX for the selection of the best parent in order improve the reliability. The Performance has analyzed by using Contiki 3.0 Cooja simulation tool. The results obtained from this research work prove that there is an enormous impact in the Quality of Service (QoS) parameters such as packet delivery ratio, throughput, latency and energy consumption with incorporation of FLOF.